EFFECT OF IMPLEMENTING THE ANDROID-BASED APPLICATION “CAKOASI.ID” (COMPLEMENTARY THERAPY DISC) ON MOTHER'S SELF-EFFICACY IN OVERCOMING BREASTFEEDING PROBLEMS - Rini Rahmayanti; Fitri Wahyuni; Hadigufri Triha (Nurse and Health, 2025)
Background: Breastfeeding coverage in Indonesia is still low, including Padang City, especially in the Andalas Health Center working area, which is 51.1%, has not reached the national target of 90%. Self-efficacy is one of the main factors in increasing exclusive breastfeeding behavior. Self-efficacy is influenced by the mother's knowledge about how to overcome breastfeeding problems. Increasing knowledge can be done through the innovation of complementary therapy disc applications that can be accessed by mothers via Android.